1980
DOI: 10.1152/physrev.1980.60.4.1107
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[alpha]pyrene metabolism, activation and carcinogenesis: role and regulation of mixed-function oxidases and related enzymes.

Abstract: I. INTRODUCTION Polycyclic aromatic hydrocarbons (PAHs) are a large class of chemicals in the atmosphere (6), soil (262), waterways and oceans, and food chain (213). Some major sources of PAHs include emissions from transportation systems, heat and power generation, refuse burning, industrial processes, and oil contamination 1107

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
554
2
6

Year Published

1987
1987
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,197 publications
(580 citation statements)
references
References 83 publications
5
554
2
6
Order By: Relevance
“…BP bioactivation in humans generates the highly toxic electrophilic metabolite (ϩ)anti-benzo(a)pyrene-7,8-dihydrodiol-9,10 epoxide (BPDE), which can damage DNA by forming DNA adducts (BPDE-DNA) through covalent binding to the amino group of guanine or adenine. 1,2 An efficient network of complementary DNA repair mechanisms is required to prevent the detrimental consequences of DNA damage, but individuals differ in their DNA repair capacity, and this may be a risk factor for cancer. 3 For example, DNA repair capacity was significantly lower in lung cancer cases than in healthy controls, the difference being especially pronounced among younger patients and smokers.…”
mentioning
confidence: 99%
“…BP bioactivation in humans generates the highly toxic electrophilic metabolite (ϩ)anti-benzo(a)pyrene-7,8-dihydrodiol-9,10 epoxide (BPDE), which can damage DNA by forming DNA adducts (BPDE-DNA) through covalent binding to the amino group of guanine or adenine. 1,2 An efficient network of complementary DNA repair mechanisms is required to prevent the detrimental consequences of DNA damage, but individuals differ in their DNA repair capacity, and this may be a risk factor for cancer. 3 For example, DNA repair capacity was significantly lower in lung cancer cases than in healthy controls, the difference being especially pronounced among younger patients and smokers.…”
mentioning
confidence: 99%
“…In particular, the association between carcinogenesis and the enzyme system responsible for the metabolism of most lypophilic chemicals, the cytochrome P-450 monooxygenases, has been addressed (1)(2)(3)(4). This enzyme system is composed of numerous cytochrome P-450 isoenzymes that differ with respect to both substrate specificities and in their responses to enzyme inducers and inhibitors (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the association between carcinogenesis and the enzyme system responsible for the metabolism of most lypophilic chemicals, the cytochrome P-450 monooxygenases, has been addressed (1)(2)(3)(4). This enzyme system is composed of numerous cytochrome P-450 isoenzymes that differ with respect to both substrate specificities and in their responses to enzyme inducers and inhibitors (1)(2)(3)(4)(5)(6). In the case of aromatic amines and amides the first and obligatory step in their metabolic activation involves N-hydroxylation, and for the model hepatocarcinogen, 2-acetylaminofluorene (AAF), we have shown that a distinct isoenzyme of cytochrome P-450 in rabbit liver is involved in this process (7).…”
Section: Introductionmentioning
confidence: 99%
“…benzo(a)pyrene (BP)] as contaminants, is responsible for the majority of incidences of human cancer. BP has been studied quite extensively as a prototype procarcinogen, whose involvement in carcinogenesis after DNA adduct formation and mutation has been fairly well documented (Gelboin, 1980; Jernstrom and Graslund, 1994). BP undergoes oxidative metabolism catalysed by cytochrome P450 lAI (CYP lAI) and NADPH:cytochrome P450 reductase (P450 reductase) to generate more than two dozen metabolites (Gelboin, 1980;O'Brien, 1991).…”
mentioning
confidence: 99%
“…Another important class of BP metabolites generated during its oxidative metabolism are the benzo(a)pyrene quinones 6-Q, BP-1,6-Q and BP-6,12-Q) (Gelboin, 1980;O'Brien, 1991). Quinones, in general, are ubiquitously found in all aerobic plants and animals and are present in the environment as part of automobile exhaust, cigarette smoke and urban air particulates (O'Brien, 1991;Monks et al, 1992).…”
mentioning
confidence: 99%